EU non-financial reporting research – insights, gaps, patterns and future agenda - Ştefănescu, Cristina Alexandrina; Tiron-Tudor, Adriana; Moise, Ecaterina Monica (Journal of Business Economics and Management, 2021)
This study approaches the fresh perspective of non-financial reporting (NFR) promoted through the Directive 2014/95/EU (EUD) by providing a state of knowledge, initiatives and approaches on this topic and also by identifying the main patterns developed within this research stream.Based on a structured literature review and statistical methods as Principal Component and cluster analysis, it investigates the progress of scientific research and design undertaken within NFR topic and discloses insights and critical issues for future research agenda.The results reveal the focus of the literature on general issues related to EUD, as well as throughout its specific requirements, using GRI or other national/international frameworks. From a methodological point of view, even though empirical studies prevailed, there are also conceptual studies that analyse the new EUD either on sampled countries or across Europe.First published online 21 December 2020